The strategies of stock management on farms in the Lublin province - Gałecka, Agnieszka (Видавництво Львівської політехніки, 2014)
Досліджено методи управління польськими фермерськими господарствами у розрізі окремих видів виробництв, вироблення стратегій їхнього розвитку. Наведено результати опитувань фермерів щодо адекватності використовуваних управлінських концепцій, в т. ч. засадних принципів управління запасами. Сформульовано окремі аспекти підвищення рівня ефективності управління запасами на польських фермерських господарствах. The paper presents opinions of farmers on strategies for the management of stocks in farms of Lublin province. The purpose of research was to define the strategies as well as the farmers’ plans concerning stock management on farms in Lublin province. The choice of farms has been intentional. The research constitutes of the entities from the Lublin province taking part in the Polish system of FADN (Farm Accountancy Data Network) which run agricultural accountancy supervised by the Institute of Agricultural and Food Economics in Warsaw (IERiGŻ-PIB). The research has been conducted with the method of direct interview on the sample of 62 farms taking part in PL-FADN. The research was conducted in 2010 with the use of questionnaire among the owners of agricultural entities of the Lublin province. The farmers could provide more than one answer to a given question. The choice of Lublin province was based on typical agricultural character of the region where agriculture is the main economy sector. The research entities were divided on the basis of agricultural type and the area. Taking agricultural type into consideration, the farms were divided into:field crops (1), other grazing livestock (including milk) (5,6), granivores (7), mixed (8). In terms of area (Agricultural Area– ha), there were four groups: small (5≤10 ha), medium-small (10≤ 20 ha), medium-large (20≤ 30ha), large (30 ≤50 ha). The horticultural (2) types of farms, wine (3), other permanent crops (4), areas up to 5 ha and over 50ha were excluded fromthe research because of their small number. The reserves constitute a significant part of property of the majority of economic entities including farms. The efficient functioning of farms depends on appropriate stock management. Agriculture is a specific sector of the economy where the stock level is kept relatively high. It results from the peculiarity of agricultural production, seasonal production and the course of vegetation conditions. Rational stock management is one of the ways to save costs. Based on the survey, it was found that the main element of circulating property in agricultural entities in the Lublin province are money resources and the store of goods and finished products with the market outlet. The highest stock level is admitted by the farmers running the entities of the area of 30-50 ha UR and of the mixed type of agriculture. It has been stated that the stock of finished products with the market outlet is the most common in case of farms specializing in the inbreeding of granivorous animals. It results from the fact that the livestock production is characterized by permanent cycles of production. The owners of agricultural entities have given the maintenance of optimum stock level as a strategy of management. It is a positive tendency which reflects the rational stock management in the agricultural entities in the Lublin province. The farmers specializing in livestock production have often given the maximizing of individual stock of agricultural products as characteristic to their strategy of stock management. It has been mostly common in case of small (5-10ha AL) and medium-small farms (10-20 ha AL). The owners of agricultural entities in the Lublin province most often plan the stock maintenance on the same level. It has been proven that they consider the past management politics of the assets as appropriate and do not need to change it. The improvement of the stock level in agricultural entities has been given to be continued in the future.
Keywords: фермерське господарство; виробництво; сільськогосподарська продукція; стратегія; управління; запаси; облік; внутрішня звітність; farm; manufacturing; agricultural products; strategy; management; inventory; accounting; internal accounting